Just cheap talk? Investigating fairness preferences in hypothetical scenarios - Paul Hufe; Daniel Weishaar (The Journal of Economic Inequality, 2025)
The measurement of preferences often relies on surveys in which individuals evaluate hypothetical scenarios. This paper proposes and validates a novel factorial survey tool to measure fairness preferences. We examine whether a non-incentivized survey captures the same distributional preferences as an impartial spectator design, where choices may apply to a real person. In contrast to prior studies, our design involves high stakes, with respondents determining a real person's monthly earnings, ranging from 500 - 5,700. We find that the non-incentivized survey module yields nearly identical results compared to the incentivized experiment and recovers fairness preferences that are stable over time. Furthermore, we show that most respondents adopt intermediate fairness positions, with fewer exhibiting strictly egalitarian or libertarian preferences. In sum, these findings suggest that high-stake incentives do not significantly impact the measurement of fairness preferences and that non-incentivized survey questions covering realistic scenarios offer valuable insights into the nature of these preferences.
Keywords: C90; D63; I39; 300; Fairness preferences; Survey experiment; Vignette studies